Critical trajectories and the timing of critique - King, Rebekka (Critical research on religion, 2018)
This editorial discusses the place of critique at different stages in research and writing. It evokes Foucault's conception of critique as transformative and draws from the symposium in this issue examining the role of critique in anthropology to shift the conversation to the question of when critique occurs. The editorial advocates for the notion of critique as a competency that is dependent upon context.